Printed zinc paper batteries - Yang, Peihua (2021)
Paper electronics offer an environmentally sustainable option for flexible and wearable systems and perfectly fit the available printing technologies for high manufacturing efficiency. As the heart of energy-consuming devices, paper-based batteries are required to be compatible with printing processes with high fidelity. Herein, hydrogel reinforced cellulose paper (HCP) is designed to serve as the separator and solid electrolyte for paper batteries. The HCP can sustain higher strain than pristine papers and are biodegradable in natural environment within four weeks. Zinc-metal (Ni and Mn) batteries printed on the HCP present remarkable volumetric energy density of ≈26 mWh cm-3 , and also demonstrate the feature of cuttability and compatibility with flexible circuits and devices. As a result, self-powered electronic system could be constructed by integrating printed paper batteries with solar cells and light-emitting diodes. The result highlights the feasibility of hydrogel reinforced paper for ubiquitous flexible and eco-friendly electronics.